Individual and organisation. Suggestions and keys to interpretation. Archipelago of essays, F. Dafano, Aracne, 2 - Cecchini, Giulia; Marini, Sara (Community Notebook. People, Education and Welfare in the Society 5.0, 2022)
The book, entitled Individuo e organizzazione, is the result of a long reflection defined by the author himself «[...] a metaphorical journey, articulated through a brief excursus on the works of some authors considered emblematic, in relation to their proposal to organise the material, conceptual or even inner reality that is the object of their commitment» (Dafano, 2014: 18). The text aims to provide an original key to the study of organisations, not only focusing on the individual in relation to the organisation, but also attempting to combine two approaches long considered antithetical: the scientific and the humanistic.